Sterrett, Joseph, and Peter Thomas, eds., Sacred Text—Sacred Space: Architectural, Spiritual, and Literary Convergences in England and Wales. Foreword Richard Chartres. Vol. 4 of Studies in Religion and Arts Series, eds. James Najarian and Eric Ziolkowski. Leiden and Boston: Brill, 2011. Pp. xvi + 372 + illustrations. $166.00 paper - Cimadomo, Guido (My University, 2020)
Two important concepts underlie this collection of essays edited by Joseph Sterrett and Peter Thomas: sacred space, a place or places where man can find “what is real in the midst of the formless expanse”; and text, considered in its sacred character, as something given to and developed by man in order to guide his own spiritual life. While they seem to proceed from opposite directions, the opposition implicit in these concepts between concrete and spiritual is not so strong when we consider that (according to Helen Wilcox) sacred spaces are everywhere when considered in the general context of the spiritual life. The relations between sacred texts and sacred spaces presented in this volume are the result of research done at Cardiff University, and are limited to England and Wales. Due to the history of the these two countries it is easy for the reader to understand how these concepts are related with the evolution and transformation of religious belief and of society in general during the period under consideration. The book is divided into three temporal sections, focusing on the medieval era, the early modern period, and the nineteenth century. The twelve essays that make up the book look at sacred texts, at sacred spaces, and at both of them in very different ways: ...
Post-refereed, pre-print version, de acuerdo con consent form. Publicado en: Religion and the Arts 19:1-2(2015). 144-145.DOI: https://doi.org/10.1163/15685292-01901011
Keywords: Lugares sagrados - Inglaterra y Gales; England; Wales; Sacred space